Efektivitas Penggunaan Google Classroom Untuk Pembelajaran Keterampilan Membaca Bahasa Jerman Kelas XI IPA 5 SMA Negeri 1 Tarik - Keziantri, Jaalani; Pujosusanto, Ari (LATERNE, 2022)
Since the COVID-19 pandemic, teaching and learning activities have been carried out online. Also applies to SMA Negeri 1 Tarik. Online learning is education that takes place through various applications, one of which is Google classroom. Google Classroom is a free application service provided by Google to facilitate teaching and learning activities between teachers and students. The problem formulation of this research is the effectiveness of using Google Classroom for learning German language class XI IPA 5 at SMA Negeri 1 Tarik, while the purpose of this study is to describe the effectiveness of using Google Classroom for learning German language class XI IPA 5 at SMA Negeri 1 Tarik. This research is a descriptive research with a qualitative approach. The data sources of this research are students of class XI IPA 5 SMA Negeri 1 Tarik. Research data are answers obtained from questionnaires that have been filled out by students. It can be seen that students can use Google Classroom, view materials, view assignments easily, and can understand "Essen und Trinken" material well. From these results, it can be concluded that Google Classroom is effectively used in learning German language.